QUANTIFICATION OF ENTEROBACTERIA AND CLOSTRIDIUM SPP. IN POULTRY SLAUGHTERHOUSES SANITARY CONVEYORS BELTS - CASAGRANDE, M. F.; POLLO, A. S.; CARDOZO, M. V.; BOARINI-FERRONI, L.; MALDONADO JUNIOR, W.; BERALDO-MASSOLI, M. C.; SCHOCKEN-ITURRINO, R. P. (Ars Veterinaria, 2018)
The increase in production and consumption of chicken meat has occurred due to modernization in this area. Such increase caused the concern about the transmission of pathogens to humans; however, with proper hygiene this transmission can be controlled. Thus, this study aimed to evaluate the pre-operational and operational hygiene in sanitary conveyors belts of chicken cuts in slaughterhouses through Clostridium spp. and Enterobacteria quantification. Statistical data analysis for Clostridium spp. colony count showed a difference between the studied slaughterhouses and the types of cleaning performed on sanitary conveyors belts (p<0,0001). Already statistical analysis for Enterobacteriaceae colony count showed significant differences only between the visited slaughterhouses (p<0,0001), with no difference between the types of conveyors belts cleaning (p=0,4057). The results showed that there was a variation in bacterial count among the slaughterhouses and the hygiene process in sanitary conveyors belts were deficient because they presented counts higher than the values recommended by the international organizations.